Sistem Informasi Akuntansi Penjualan, Piutang, dan Penerimaan Kas pada PT Nakami Kinema Cemerlang - Sukendar, Heri; Selvia, Selvia (Bina Nusantara University, 2010)
PT Nakami Kinema Cemerlang is one of Indonesia`s telecommunication infrastructure contractor company. The company businessâ process is into BTS (Base Transceiver Station) infrastructures projects, which engaged in the construction and erection of telecommunication towers, BTS CME works and SITAC projects. Currently, the company is faced with the issues in negligence according to account receivable recording and billing processes. these are because the performance onÂ the current system is not maximized in terms of efficiency and effectiveness. Therefore, the writer will conduct an analysis on the existing system and to design a proposed new system. The new Accounting Information Systems on Sales, Receivables, and Cash receipts will cover the process of recording documents on the project contracts, project sales orders, demand for material requirements, the status updates of project development, billing progress for the completed project phases right up to the receipt payments. By the data processing, information will be presented in the form of reports to managers in need of management purposes and board of directors to support decision making.Â